Analysis of The Predicted Volume of Domestic Household Waste in the Communities of Das Bila and Its Impact on The Siltation of Lake Tempe - Akbar Sudarmo; Eddy Setiadi Soedjono (Journal of Social Research, 2023)
The substantial waste production in the Bila watershed poses a severe threat to the area. This not only negatively affects the environment but also leads to sediment buildup in Lake Tempe. Managing the lake's health entails not solely addressing the lake itself, but also evaluating the impact within the encompassing river basin. This research examines the anticipated waste volume that could potentially contribute to sedimentation in Lake Tempe. The approach taken employs spatial analysis, utilizing a 20-meter buffer surrounding the water body. This buffer represents the zone within which the population is assumed to dispose of waste into the river. The accuracy of the findings was verified through interviews with residents residing within this 20-meter radius. The predominant source of the waste responsible for sedimentation is inorganic in nature, as it doesn't undergo natural decomposition. The study's projection suggests that by 2031, the cumulative volume of waste-triggered sedimentation will reach 1408.63 cubic meters. Addressing the burgeoning waste issue in the Bila watershed is paramount to preserving the integrity of Lake Tempe. By adopting a comprehensive perspective that encompasses both the lake and its surrounding river basin, effective strategies can be devised to mitigate sedimentation and ensure the longevity of this crucial ecosystem.